1994
DOI: 10.1007/bf00234482
|View full text |Cite
|
Sign up to set email alerts
|

Elevation in intracellular calcium activates both chloride and proton currents in human macrophages

Abstract: The transition of a resting macrophage into the activated state is accompanied by changes in membrane potential, cytoplasmic pH, and intracellular calcium (Ca(i)). Activation of Cl- as well as H(+)-selective currents may give rise to stimulus-induced changes in membrane potential and counteract changes in intracellular pH (pHi) which have been observed to be closely associated with respiratory burst activation and superoxide production in macrophages. We carried out whole-cell voltage clamp experiments on huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…The CaMKII-dependent anion current was absent in vector-transfected tsA cells, and was blocked by the CaMKII specific inhibitor, autocamtide-2-related inhibitory peptide. The relative lyotropic anion permeability (P X /P Cl ) of wild type hClC-3 was I Ϫ Ͼ Br Ϫ Ͼ Cl Ϫ and is consistent with previous reports of I Cl,CaMKII from different laboratories (3,16,(25)(26)(27). To confirm that I Cl,CaMKII is directly mediated by hCLC-3 and not due to activation of an ion channel endogenous to tsA cells, a mutation in hCLC-3 (G280E) was made and transiently expressed in tsA cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The CaMKII-dependent anion current was absent in vector-transfected tsA cells, and was blocked by the CaMKII specific inhibitor, autocamtide-2-related inhibitory peptide. The relative lyotropic anion permeability (P X /P Cl ) of wild type hClC-3 was I Ϫ Ͼ Br Ϫ Ͼ Cl Ϫ and is consistent with previous reports of I Cl,CaMKII from different laboratories (3,16,(25)(26)(27). To confirm that I Cl,CaMKII is directly mediated by hCLC-3 and not due to activation of an ion channel endogenous to tsA cells, a mutation in hCLC-3 (G280E) was made and transiently expressed in tsA cells.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies on the characterization of the CaMKIIactivated anion conductance carried out in our laboratory as well as others have shown that I Cl,CaMKII is outwardly rectifying (8, 11, 12, 14 -16, 25), is inhibited in the presence of 500 M DIDS (16,25), and has a P I /P Cl ratio greater than 1 in airway cells (25,26) and human macrophages (16). In this paper, we have cloned and expressed the human isoform of the CLC-3 gene and shown that its properties are identical to the endogenous I Cl,CaMKII in cells of both airway and gastrointestinal origin.…”
Section: Discussionmentioning
confidence: 73%
“…Thioglycolate-recruited mouse peritoneal cells dialyzed in K + -glutamate containing InsP 3 showed a rapidly activating outward current that depolarized the cells, suggesting that part of the current was carried out by Cl - (Judge et al, 1994). In human monocyte-derived macrophages, rises of [Ca 2+ ] i induced an I Cl current of properties similar to those described previously, and sensitive to www.intechopen.com DIDS (Holevinsky et al, 1994). A third of the total current recorded in our model was inhibited by DIDS involving an anion, most probably Cl - (Camacho et al, 2008).…”
Section: Macrophage Ion Currentssupporting
confidence: 63%
“…In cells of haematopoetic origin, CaCC currents have been characterized in neutrophils [66], macrophages [67], Jurkat lymphocytes [68] and human mast cell line HMC-1 [69]. In these studies CaCCs were activated by Ca 2+ ionophore or by dialyzing the cell [55].…”
Section: +mentioning
confidence: 99%